PERAN ORANG TUA TERHADAP PEMBENTUKAN AKHLAK SEORANG ANAK MENURUT PERSFEKTIF HADIS - Alkurnie, Muhammad Iqbal; Sulidar (Ulumuna: Jurnal Studi Keilsman, 2024)
Moral education in children is a crucial aspect in shaping their character, which begins within the family as the first environment where children learn. This study discusses the role of parents in the formation of a child's morality from the perspective of hadith, emphasizing the importance of balanced parenting between freedom and boundaries. Using a qualitative approach, this research employs library research and field study methods to analyze relevant hadiths from the Kutub al-Sittah, supplemented by observations and interviews. The findings indicate that parents play a central role in educating their children, as children tend to imitate their parents' behavior. An overly strict parenting style can hinder communication and encourage dishonest behavior, while a more flexible and attentive approach tends to produce children who are open, sociable, and emotionally intelligent. However, unregulated freedom can negatively impact a child's moral development. Therefore, a balance between granting freedom and establishing clear boundaries is essential to ensure the positive moral development of children. This study underscores the importance of the parental role in guiding children to maintain a balance between internal influences (family) and external influences (social environment).